2017
DOI: 10.1002/smr.1927
|View full text |Cite
|
Sign up to set email alerts
|

Using agile methods for the development of green and sustainable software: Success factors for GSD vendors

Abstract: Over the last decade, the use of agile methods has grown dramatically for software development.Agile methods guarantee to accelerate the delivery of remarkable software with increased user satisfaction and reduced cost. However, in recent years, due to the emergence of green software engineering, software developers are compelled to focus more on green and sustainable aspects of software. Green software engineering aims to design, develop, and use the software with confined energy and computing resources. Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…As an example, consider the four characteristics: A, B, C, and D, in descending order of frequencies with equal frequencies for B and C ( A > B = C > D ); based on the approach used, A is assigned the rank 1 and an average rank of 2.5 is assigned to characteristics B and C. Characteristic D has the next highest value and has therefore been given the rank of 4. This approach has already been used by other researchers for calculating rankings in similar research works Rashid and Khan, 2017 ). In order to specify the significance of the similarity between the ranks of characteristics in the SMS and the ranks in the questionnaire survey, specific descriptive statistics were used, as explained in Section 4.4 .…”
Section: Analysis Of Sms and Survey Datamentioning
confidence: 99%
“…As an example, consider the four characteristics: A, B, C, and D, in descending order of frequencies with equal frequencies for B and C ( A > B = C > D ); based on the approach used, A is assigned the rank 1 and an average rank of 2.5 is assigned to characteristics B and C. Characteristic D has the next highest value and has therefore been given the rank of 4. This approach has already been used by other researchers for calculating rankings in similar research works Rashid and Khan, 2017 ). In order to specify the significance of the similarity between the ranks of characteristics in the SMS and the ranks in the questionnaire survey, specific descriptive statistics were used, as explained in Section 4.4 .…”
Section: Analysis Of Sms and Survey Datamentioning
confidence: 99%
“…It has been shown that agility plays an important role in the development of sustainable design [20][21][22][23]. However, there is still much uncertainty surrounding the application of agility in sustainable design, including the processes involved and its potential benefits.…”
Section: Introductionmentioning
confidence: 99%
“…One of the components of the model is the identification of critical success factors (CSFs) and its related practices. We have identified the CSFs and have been published . In this paper, we have presented 36 agile practices identified through systematic literature review (SLR) and survey.…”
Section: Introductionmentioning
confidence: 99%
“…We have identified the CSFs and have been published. 48 In this paper, we have presented 36 agile practices identified through systematic literature review (SLR) and survey.…”
Section: Introductionmentioning
confidence: 99%